Effect of different varieties and FYM levels on yield and quality of onion (Allium cepa L.) in rid westem Rajasthan (Indian Journal of Arid Horticulture, 2017)
An experiment was conducted during rabi season of 2009-2010 at Horticulture Farm, Swami Keshwanand RajasthanAgricultural University, Bikaner. The experiment comprising of four varieties of onion viz., PDR, RO-59, RO-252 and RO-282 and FYM levels viz., 0, 20, 40 and 60 t ha-. A total of 16 treatment combinations were evaluated in randomized blockdesign with three replications. The results indicated that plant height, number of leaves per plant, moisture content of bulb,neck thickness, diameter of bulb, volume of bulb, bulb yield, TSS and N, P and K uptake were maximum under the varietyRO-252. Application of FYM @ 40 t/ha significantly increased number of leaves per plant, moisture content of bulb, neckthickness, diameter of bulb, volume of bulb, bulb yield, TSS, Pungency and N, P and K content and uptake however, plantheight at 60 DAT was maximum with the application of 60 t FYM/ha.
Keywords: Bulb; Farm Yard Manure; moisture; onion; varieties and volume